PERAN HAKIM PENGAWAS DAN PENGAMAT BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1981 TERHADAP POLA PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN PEKANBARU - Destuti Situmorang; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In addition to checking, hearing and deciding the case in court, the judge also has the task of monitoring and observation coaching inmates at the Correctional Institution. The judge in charge of overseeing and observing the inmates called the Supervisor and Observer Judge contained in the Code of Criminal Procedure Article 277-283. But this time, the judge was only carrying out its mission in the Court, then later handed over to the inmates of correctional Institution. Supervision and observation of prisoners conducted so far have not been going well. The purpose of this thesis, namely: First, Implementation Role Supervisor and Observer Judge Against Development of Prisoners in Penitentiary Class IIa Pekanbaru, Second, Obstacles Faced By Supervisor and Observer Judge In Supervise and watching inmates at the Correctional Institution Class IIa Pekanbaru, Third, efforts ducted by Supervisor and observer Judge To Improve Monitoring and Observation Prisoners in Penitentiary Class IIa Pekanbaru.This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in the District Court of Pekanbaru and at the Correctional Institution Class IIa Pekanbaru, while the sample population is a whole party with regard to the problems examined, the data source used, primary data, secondary data and data tertiary, data collection techniques in this study with interviews and literature study.From the research of this problem has three main things that can be inferred. First, the role of Supervisor and Observer Judge not run well in Class IIa Pekanbaru Penitentiary. Second, the constraints faced by the Supervisor and Observer Judge that the busy schedule of judges in the courts, the number of Supervisor and Observer Judge only 1 (one), the absence of the auxiliary staff of the judges, the absence of a given budget. Third, efforts were made which will maximize the time to execute the duties of men, increase the number of Supervisor and Observer Judge or auxiliary staff.Keywords: Role - Supervisor and Observer Judge - Inmates Coaching